Chemical Composition and Antimicrobial Activity of Subcritical CO2 Extract of Lepidium latifolium L. (Brassicaceae) - Balzhan B. Azimkhanova; Gulbaram O. Ustenova; Kamalidin O. Sharipov; Kayrolla D. Rakhimov; Galiya M. Sayakova; Ardak B. Jumagaziyeva; Elena V. Flisyuk; Nadezhda G. Gemejiyeva (International Journal of Biomaterials)
The genus Lepidium L. from Brassicaceae Burnett. family covers over 150 species with an almost cosmopolitan spread. In Kazakhstan, 21 species are described, of which four species are characterized by medicinal properties (L. crassifolium Waldst. et Kit., L. perfoliatum L., L. ruderale L., and L. latifolium L.), used in folk medicine as means of antibacterial, irritant, laxative, antitumor, analgesic, and anthelmintic action. Methods. Raw materials were collected from Almaty region (Republic of Kazakhstan). Lepidium latifolium L. herb’s carbon dioxide extract (CO2 extract) was obtained by subcritical carbon dioxide extraction. A gas chromatograph with a mass spectrometric detector was used to determine the component composition of the extract. Antimicrobial activity was determined by two methods: the micromethod of serial dilution and the disc-diffusion method. Four microbial test strains were used: Staphylococcus aureus ATCC 6538-P, Escherichia coli ATCC 8739, Klebsiella pneumonia ATCC 10031, and Candida albicans ATCC 10231. Results. The technology of carbon dioxide extraction has undoubted advantages over traditional methods of extraction: it has a controlled selectivity in relation to groups of biologically active substances, allows deep extraction, and maximizes the release of rich complexes of compounds contained in plants. In this study, firstly, the CO2 extract was obtained under subcritical conditions from the aerial part of L. latifolium L., and the composition was determined. Hexane was the best solvent for CO2 extract, and 40 components were identified. Screening of antimicrobial activity of the L. latifolium’s CO2 extract showed the essential activity of all clinically significant strains tested: Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, and Candida albicans. Conclusions. This research showed that the CO2 extract of the raw material of Lepidium latifolium L. contains biologically active compounds exhibiting an essential antimicrobial effect, and therefore it is possible to recommend for the development of various drugs for use in medical practice.